Kualitas Organoleptik dan Kandungan Gizi Kerupuk Ikan Lokal (Bleberan) Formulasi sebagai Camilan untuk Balita Stunting: Organoleptic Quality and Nutritional Content of Local Fish (Bleberan) Formulation Crackers as Snacks for Stunting Toddlers - Mahyuddin, Meriwati; Rizal, Ahmad; Afrizal, Afrizal (Amerta Nutrition, 2024)
Background: Toddlers commonly experience nutritional problems due to a variety of factors such as direct, indirect, main, and basic factors. Stunting is a chronic malnutrition problem that can have both long and short-term impacts on toddlers. The Bengkulu area is predominantly located along the coast, boasting an abundance of marine products. There are certain types of small fish that are considered byproducts and relatively inexpensive. Objectives: This study aimed to assess the hedonic test for fish crackers with a variety of vegetables (mustard greens, carrots, and apple tomatoes) using a hedonic test. Methods: This study was conducted in the Nutrition Laboratory for 1 month start with product manufacturing, organoleptic and acceptability tests carried out at selected public health centres that had the highest stunting criteria. The selected public health centres are Pasar Ikan, Beringin Raya, Sawah Lebar, Penurunan, Anggut Atas, Sukamerindu, and Jalan Gedang. This study was a completely randomized design (CRD). Data were analysed using the Stata 16, conducting univariate analysis (proportions and averages). Results: The fish crackers with apple tomatoes variant, composed of 250 g of fish and 50 g of apple tomatoes, showed the highest average score among other variants. This formulation had 424.42 kcal and 0.96 g ) between the four variants. Conclusions: The formulation of bleberan fish crackers with tomato showed the highest preference score with an average value of 3.83, with a significant difference in the quality of the colour.